Low Power Active Electrode ICs for Wearable EEG Acquisition - Xu, Jiawei (Analog Circuits and Signal Processing,, 2018)
This book presents fundamental requirements, electrical specification, and parameter tradeoffs of wearable EEG acquisition circuits, especially those compatible with dry electrodes for user-friendly recordings. The authors introduce active electrode, the most promising solution for dry electrodes-based EEG measurement. This architectural concept has been combined with various, innovative circuit design techniques to illustrate structured IC design methodologies for high performance EEG recording. This book also gives examples on the design, implementation and evaluation of three generations of active electrode ICs.